2021
DOI: 10.1007/s10340-021-01471-3
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to amitraz in the parasitic honey bee mite Varroa destructor is associated with mutations in the β-adrenergic-like octopamine receptor

Abstract: Varroa destructor is considered a major reason for high loss rate of Western honey bee (Apis mellifera) colonies. To prevent colony losses caused by V. destructor, it is necessary to actively manage the mite population. Beekeepers, particularly commercial beekeepers, have few alternative treatments other than synthetic acaricides to control the parasite, resulting in intensive treatment regimens that led to the evolution of resistance in mite populations. To investigate the mechanism of the resistance to amitr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 79 publications
0
22
0
1
Order By: Relevance
“…Amitraz has been the most widely used miticide to control for Varroa mites for the last 20 years, even though some studies have documented mite populations that are now resistant to amitraz in the U.S. [ 34 , 31 ], Argentina [ 101 ], Czechia [ 102 ], and France [ 103 ]. Given the importance of amitraz as the main “go-to” miticide in U.S. commercial beekeeping operations, more studies looking at the non-target effects of amitraz exposure on honey bees are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Amitraz has been the most widely used miticide to control for Varroa mites for the last 20 years, even though some studies have documented mite populations that are now resistant to amitraz in the U.S. [ 34 , 31 ], Argentina [ 101 ], Czechia [ 102 ], and France [ 103 ]. Given the importance of amitraz as the main “go-to” miticide in U.S. commercial beekeeping operations, more studies looking at the non-target effects of amitraz exposure on honey bees are needed.…”
Section: Discussionmentioning
confidence: 99%
“…55 Resistance to amitraz has been reported worldwide, and the mechanisms responsible for the lack of efficacy have attracted extensive interest. 56,57 Previous studies have identified mutations that might associate with resistance, 22,58,59 therefore identifying the reason for the effectiveness of amitraz against Varroa mites but its low toxicity to honeybees is useful to research amitraz resistance. The key determinant of the drug efficacy of orthosteric drugs is a high affinity, and the enhanced amitraz activation of Oct⊎2R by mutations is valuable for designing more rational drugs to control Varroa mites.…”
Section: The Ligand Amitraz Slightly Prefers To Bind With the Mutativ...mentioning
confidence: 99%
“…Amino acid replacement of octopamine/tyramine receptors (T8P, L22S, and A181T) leading to amitraz resistance have been reported in Rhipicephalus microplus 20,21 . A more recent study evidenced that amino acid substitutions N87S or Y215H in the Octβ2R might be associated with the resistance to amitraz in V. destructor 22 . A previous study found that the relative insensitivity of honeybee Octβ2R to amitraz was vital for the application of amitraz, but combinatorial mutations (E208V, I335T, and I350V) increased the sensitivity of honeybee Octβ2R to amitraz through a pharmacological profile and transgenic flies expressing Octβ2R variants assays 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Este ácaro foi observado pela primeira vez nas abelhas da espécie Apis cerana. Nesta espécie, as varroas causam danos ligeiros, pois o seu crescimento populacional era limitado, pois só se reproduzem nos alvéolos de zangão (Hernández-Rodríguez et al, 2022). Em meados do século XX, este ácaro passou a infestar colónias de Apis mellifera, evidenciando uma maior eficiência reprodutiva nesta espécie de abelhas, pois conseguem reproduzir-se tanto nos alvéolos de zangão como nos de obreiras (Beaurepaire et al, 2015).…”
Section: Introductionunclassified